AMERICAN, CHINESE AND RUSSIAN FACTORS IN INTERACTION OF CENTRAL AND SOUTH ASIAN STATES - Rudenko Yelena I. (Scientific Journal of Pedagogy and Economics, 2019)
The paper aims at brief analytical consideration of ‘external powers’ factor as either true or false materialization of would-be scientific concept of the ‘New Great Game’ through the prism of South Asian states’ interests in view of their interaction with the republics of Central Asia. The research presented in the paper is performed on the basis of analysis of works and oral statements on this issue by Indian and Pakistani scholars and experts over the past quarter century. Taking into account a complex of historical-geographical and politicaleconomic reasons, the main attention is paid to the role and place of states such as the United States of America, the People’s Republic of China and the Russian Federation. Through a brief sum-up of specific situations and examples, it is shown that for each of these three powers the representatives of India and Pakistan have virtually a full range of positive, neutral and negative theoretical calculations and practical experience that determine their final assessment of actual significance of ‘external factor’ in relations between their countries and Central Asian republics. In conclusion, it is argued that despite true-to-life presence of a number of features of the ‘New Great Game’ in Central Asian region, this phenomenon nevertheless did not receive its full materialization principally because of increasingly consolidated actual status of Central Asian states as subjects rather than objects of international relations.